Pengaruh green advertising, green brand trust, dan sikap pada green product terhadap green purchase intention - Bunga Alfausta Amallia; Mohamad Irhas Effendi; Abdul Ghofar (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2022)
The environment is currently of concern because it has been damaged, this is greatly influenced by human life so that it encourages changes in consumer behavior to become more aware of the environment and interested in buying green products. This study aims to determine and analyze the role of attitude as a mediator and the effect of green advertising, green brand trust and attitudes towards green purchase intention. Data collection instruments used a questionnaire and obtained a sample of 118 respondents using a purposive sampling technique. Data were analyzed using descriptive and quantitative statistical analysis. Research using PLS-SEM analysis tools using the Smart PLS software program 3.2.8. The results showed that green advertising, green brand trust and attitude towards green product variables had a significant and positive influence on green purchase intention and green product attitude variables fully influenced the green advertising variable, green brand towards green purchase intention.